Dampak Kekuatan Informasi Film Ngenest terhadap Penilaian Komunitas Stand Up Indonesia di Jakarta - Rustono Faradi Marta; Angelina Suryani (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2016)
This research examines the influence of information strength on NGENEST The Movie towards social judgment. This topic has appointed based on facts that the delivery of anti-discrimination message is expected can inffluence Indonesian people about Bhinneka Tunggal Ika (unity in diversity). The purpose of this study is to find effects of a message on NGENEST The Movie towards social judgment. This research is using quantitative method with positivistic and explanative approaches .Data were colected through by questionnaires to 91 members of Stand Up Indonesia community in Jakarta, and supported by secondary data obtained from literature. Hypotheses testing has been done by doing correlation test, regression, coefficient of determination and t-test. The result shows that information strength on NGENEST The Movie has significant relation towards social judgment. The result of linear regression has been indicated by equation Y = 3,037 + 0,365 X1, with the result of hypotheses testing stating that the variable of information strength on NGENEST The Movie has significant impact on social judgment, contributing to 17,9 %. It can be concluded that the information strength on NGENEST The Movie has significant impact towards social judgment.